2012
DOI: 10.1155/2012/630543
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis of Cholangiocarcinoma

Abstract: Epidemiological data from the last years show an increasing trend of incidence and mortality of cholangiocarcinoma (CC) worldwide. Many pathophysiologic aspects of this neoplasia are still unknown and need to be fully discovered. However, several progresses were recently made in order to establish the molecular mechanisms involved in the transformation and growth of malignant cholangiocytes. The principal concept that at least seems to be established is that cholangiocarcinogenesis is a multistep cellular proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 68 publications
0
35
0
1
Order By: Relevance
“…In recent years, many studies have shown that COX-2 is overexpressed in bladder, non-small cell lung, and gastric cancers (Grammas, 2011;Fukuhara et al, 2013;Rosas et al, 2014;Thomas, 2014). Additional studies showed that COX-2 expression was closely associated with local angiogenesis, tumor cell infiltration, proliferation, and apoptosis (Grammas, 2011;Fava and Lorenzini, 2012;Fukuhara et al, 2013;Rosas et al, 2014). VEGF is the most important factor in angiogenesis and has been widely investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many studies have shown that COX-2 is overexpressed in bladder, non-small cell lung, and gastric cancers (Grammas, 2011;Fukuhara et al, 2013;Rosas et al, 2014;Thomas, 2014). Additional studies showed that COX-2 expression was closely associated with local angiogenesis, tumor cell infiltration, proliferation, and apoptosis (Grammas, 2011;Fava and Lorenzini, 2012;Fukuhara et al, 2013;Rosas et al, 2014). VEGF is the most important factor in angiogenesis and has been widely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Its prognosis is generally poorer than other malignancies such as gastric cancer and colorectal cancer (Fava and Lorenzini, 2012;Aishima et al, 2013;Marino et al, 2013). Thus, it is important to identify new treatments for cholangiocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-6 (IL-6) seems like a critical signaling molecule in the pathogenesis of various cancers and can be found upstream or downstream of several other oncogenes [17][18][19][20][21]. In this context, the CC is no exception, and IL-6 is a key cytokine in the pathogenesis of this neoplasm being its proliferative effect confirmed ( Fig.…”
Section: Molecular and Genetic Alterationsmentioning
confidence: 99%
“…Le mauvais pronostic de ces tumeurs s'explique par le diagnostic tardif qui est souvent fait à un stade avancé de la maladie, inopérable ou métastatique, et par l'absence de traitement standardisé efficace. Ces dernières années, les recherches se sont donc appliquées à décrire les mécanismes molécu-laires de la carcinogenèse des CVB afin d'identifier de nouvelles pistes pour d'éventuelles thérapies ciblées [9]. La capacité à identifier les différents sous-types moléculai-res sera cruciale pour progresser dans la prise en charge des CVB.…”
Section: Cancer Des Voies Biliaires (Cvb)unclassified